Climatic hazards and water management in the Mediterranean region - Sehmi N.S. (Aspects économiques de la gestion de l'eau dans le bassin méditerranéen, 1997)
The Mediterranean Sea basin lies in the transitional zone which falls under the influence of the subtropical high-pressure system during the summer and under the temperate low-pressure system during winter, drawing in cyclonic depressions from the Atlantic Ocean. These depressions penetrate almost unobstructed the entire length of the Mediterranean Sea to the Middle East and beyond. The Mediterranean climate produces many beneficial effects which, throughout the ages, have led to economic progress, stemming from the flowering of a succession of centre of civilization. The extremes of this climate, however, have often turned into destructive forces, manifesting themselves in the form of rainstorms, severe thunderstorms, snow storms, floods, droughts and dust storms. This destructive impact has increased over the years on account of the growing population and expanding economy. The climatic hazards in this region sometimes coincide with other natural disaster-producing forces such as volcanic eruptions, earthquakes, and landslides, as well as with man-made events such as accidental air and water pollution. This paper looks into the origin and nature of the climatic hazards, mitigation of their impacts, and proposes cooperative regional studies and projects
Atelier sur les Aspects Economiques de la Gestion de l'Eau dans le Bassin Méditerranéen, 1995/05/17-19, Marrakech (Morocco)